Sol–gel synthesis of microporous carbon using resorcinol and formaldehyde. (1st April 2016) - Moussaoui, Rebah; Mosbah, Mongi Ben; Elghniji, Kais; Elaloui, Elimame; Moussaoui, Younes
Microporous carbon materials were prepared by thermal decomposition of a xerogel. The xerogel was synthesised through polycondensation of resorcinol and formaldehyde using an acid-catalysed sol–gel method. Acetic acid (1 M) was used as a catalyst. The effect of the molar ratio of resorcinol/catalyst (10/3, 5, 10, 20) on the obtained hydrogel was studied. The temperature range 25–110 °C was used to convert the hydrogel into a solid resorcinol/formaldehyde xerogel. The optimum molar ratio of resorcinol/catalyst was found to be 10/3. The dried xerogels were pyrolysed under an argon atmosphere at 800 °C to obtain microporous carbon materials with a uniform structure consisting of hollow particles and a specific surface area of 650 m2 g–1.